2020
DOI: 10.1016/j.ecoenv.2019.109904
|View full text |Cite
|
Sign up to set email alerts
|

A rapid and simple fluorescence enzyme-linked immunosorbent assay for tetrabromobisphenol A in soil samples based on a bifunctional fusion protein

Abstract: Tetrabromobisphenol A (TBBPA) is the largest brominated flame retardant which can be released to environment and cause long-term hazard. In this work, we developed a rapid and highly sensitive fluorescence enzyme-linked immunosorbent assay (FELISA) for monitoring of TBBPA in soil samples. TBBPA specific nanobody derived from camelid was fused with alkaline phosphatase to obtain the bi-functional fusion protein, which enable the specific binding of TBBPA and the generation of detection signal simultaneously. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Previous studies have reported that VHHs show high affinity to free analytes in buffers with high concentration of organic solvent. 32,44,45 In this study, although VHHjd8 and VHHjd8-BT showed a high titer by using organic solvents (Figure 4A,C), no affinity improvement to fenitrothion was observed compared with mAb (Figure 4B,D). It was assumed that the high titer observed for VHHs in organic solvents might not be attributed to the high affinity to coating antigens but caused by nonspecific adsorption or other unclear mechanisms.…”
Section: ■ Discussionmentioning
confidence: 53%
“…Previous studies have reported that VHHs show high affinity to free analytes in buffers with high concentration of organic solvent. 32,44,45 In this study, although VHHjd8 and VHHjd8-BT showed a high titer by using organic solvents (Figure 4A,C), no affinity improvement to fenitrothion was observed compared with mAb (Figure 4B,D). It was assumed that the high titer observed for VHHs in organic solvents might not be attributed to the high affinity to coating antigens but caused by nonspecific adsorption or other unclear mechanisms.…”
Section: ■ Discussionmentioning
confidence: 53%
“…In the diagnostics fields, Nb have been used for imaging diagnostics, especially in cancer diagnostics . Moreover, the number of publications about nanobodies for the detection of low-molecular-weight molecules is increasing particularly for pesticides , and toxins. , Nanobodies for aflatoxin B1 detection have been characterized, showed good performance, and demonstrated the ability to be expressed as a fusion protein to nanoluciferase and alkaline-phosphatase…”
Section: Introductionmentioning
confidence: 99%
“…Such specialized biosensors are usually limited to detect the same type or specific targets. Enzyme-linked immunosorbent assay (ELISA), as a broad-spectrum immunoassay, can convert the antigen–antibody interactions into readable color changes by the enzyme-labeled antibody, which has been regarded as a gold standard for ligand (protein) detection in clinical diagnosis, food safety, , and environmental monitoring , for its high specificity and simplicity. Its detection sensitivity is highly dependent on the catalytic activity and loading of the enzyme. , Although natural enzymes have advantages of high catalytic activity, substrate specificity, and mild reaction conditions, the catalytic activity often suffers from environmental conditions and low stability due to denaturation and digestion.…”
Section: Introductionmentioning
confidence: 99%